SIRI’ NA PACCE DAN IDENTITAS KEBUDAYAAN - Fajrul Ilmy Darussalam (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2021)
This research is entitled siri'na pacce and cultural identity, which will seek to provide an alternative perspective in understanding the cultural values of the Bugis-Makassarese people. The concept of siri' na pacce is a philosophy of life that is always upheld by the Bugis-Makassar people, which literally means shame and pain. This concept has a big role in various aspects of the life of the Bugis-Makassar people. This research will understand the concept comprehensively as a cultural identity.This research is a literature research related to a concept in history. This research was conducted in an effort to discuss the concept of siri' na pacce as a material object and the perspective of cultural identity as a formal object, so as to produce an adequate inventory of literature, produce a synthesis related to a concept or thought, and provide alternatives related to understanding a concept or thinking. This study uses methodical elements such as description, interpretation, internal coherence, and idealization.The results of this study are that siri' na pacce as a cultural concept is certainly in line with several main functions of culture as an identity such as the identity meaning function, group inclusion function, the ecological adaptation function, and the cultural communication function. This then shows that the concept of siri'na pacce can continue to exist along with the times from generation to generation.